A practical tutorial programme for first-year university students: impact of its academic recognition / Un programa tutorial práctico en alumnos universitarios de nuevo ingreso: incidencia de su reconocimiento académico. Issue 1 (2nd January 2016) - Ordóñez-Solana, Celia; Pérez-López, María-Carmen; Argente-Linares, Eva
Abstract: The task of guiding and tutoring in higher education contributes to increasing the quality of teaching at university. Students who access university studies require specific guidance which is different from that required by more senior students. The aim of this study is to present a comprehensive model of tutorial guidance. The model seeks to satisfy the specific needs of first-year university students, both in terms of personal support and formative and informative support, through a set of coordinated activities during the first year of their degree. The teaching experience carried out demonstrates the students' interest in the tutoring programme offered, and measures the impact that its academic recognition has in terms of students enrolling on and following the programme. The methodology used shows the characteristics of the programme introduced and then shows the results obtained, which are discussed in relation to the research objectives.